(untitled) (Bangladesh Journal of Medical Science, 2026)
Backgroun Healthcare professionals, particularly physicians who prescribe radiological examinations, must have a solid understanding of ionizing radiation principles, their biological effects, and the various preventive measures associated with them. This knowledge is essential to avoid unnecessary patient exposure and to mitigate these effects when deemed appropriate. The development of a tool capable of assessing physicians’ understanding and knowledge of radioprotection represents a key strategy for strengthening a culture of safety and optimizing clinical practices. Objective This study aims to design and validate the psychometric properties of a questionnaire assessing prescribing physicians’ knowledge of ionizing radiation effects and radioprotective agents. Methods A cross-sectional study design was adopted for this research. Initially, a 35- item questionnaire was developed, covering two domains: (a) effects of ionizing radiation and (b) radioprotective agents. Face validity and content validity were assessed by a panel of nine experts. Analyses were conducted to determine content validity indices in terms of relevance and clarity (I-CVI, S-CVI/ Ave, and S-CVI/UA), as well as the content validity ratio (CVR). Data were collected from 134 physicians across various specialties. Internal consistency was measured using the KR-20 coefficient (Kuder-Richardson Formula 20), and temporal stability was evaluated using the test-retest method (kappa coefficient). Results The finalized questionnaire includes 24 items that were validated by experts. The indices obtained were I-CVI ≥ 0.78, S-CVI/UA = 0.98, and S-CVI/Ave = 0.91, confirming excellent relevance and clarity. Regarding internal consistency reliability, the KR-20 coefficients were 0.746 (radiation effects) and 0.62 (radioprotective agents), with an overall score of 0.802. The kappa coefficients were reported at 0.84 and 0.834, respectively, with a range of 0.74 to 0.98 across all questionnaire items. Conclusion The results provide strong evidence supporting the validity and reliability of the developed questionnaire, characterized by commendable content validity indices, satisfactory internal consistency, and near-perfect kappa coefficients. Further studies are needed to extend its validation to other populations and geographic contexts, and to explore its usefulness in assessing the impact of educational interventions. BJMS, Vol. 25 No. 01 January’26 Page : 214-229